Civilians in war - Chesterman, Simon (Lynne Rienner Publishers, 2001)
This title seeks to expand the tools available to international actors endeavouring to protect civilians in times of war. It presents a range of perspectives on the evolving norms of international humanitarian law and humanitarian actors can persuade belligerants to respect those norms.